PENGUATAN PEMAHAMAN YUDISIAL REVIEW PERATURAN DAERAH DI MAHKAMAH AGUNG KEPADA PIMPINAN DAN ANGGOTA DPRD KABUPATEN DEMAK - Junaidi, Muhammad; Fridatien, Ericke (Jurnal Abdimas Bina Bangsa, 2025)
Judicial review which is the process of testing regulations under the law is very important, but until now the nature of the test in the procedural law is closed. This is a problem considering the concept of open regulations that contain the meaning of the principle of legal fiction that everyone must understand and follow, but in the process of formation is closed. On the other hand, understanding for DPRD members is certainly important regarding the judicial review mechanism because it is the legal basis for the implementation of regional government. In the findings of the community service activities carried out, it shows that the existence of a mechanism for the concept of judicial review of regional regulations has not been widely understood by DPRD members. The purpose of understanding is of course to provide openness and caution for DPRD members so that the formation of regional regulations in the future is in accordance with the rules stated in the regulations on the procedures for the formation of laws and regulations. Suggestions for future community service activities to continue to be carried out by community service to DPRD members in order to emphasize that every regional legal product must be examined for norms so that later it will not be easily canceled in the Supreme Court through the judicial review process mechanism.